Aggression in crime and sports: a study on prisoners and amateur combat athletes in Türkiye - Muhammed Sıddık Çemç; Enes Madak; Özgür Gülen; Hüseyin Ozan Sönmez (BMC Psychology)
Abstract Background This research focuses on examining and comparing the aggression levels of prisoners incarcerated for intentional injury and amateur combat athletes. The study aims to explore the differences in aggression levels among these groups to understand the impact of incarceration and sports participation on aggression. Methods The participants included in the analysis consist of prisoners (n = 363) housed in Marmara No. 7 and No. 3 Type L Closed Penal Institutions, who have been incarcerated for intentional injury, with an average age of 36.64 ± 10.30 years and an average custody period of 980.47 ± 1335.27 days. Amateur combat athletes (n = 203) with an average age of 25.17 ± 10.09 years have been actively engaged in sports for an average of 11.83 ± 9.53 years. The control group (n = 329) has an average age of 32.65 ± 7.56 years. Data collection instruments included a personal information form and the Buss-Perry Aggression Questionnaire. The data were analyzed using IBM SPSS Statistics 23.0, with a significance level set at p < 0.05. Results Analysis of the Buss-Perry Aggression Questionnaire scores revealed that the aggression levels of prisoners incarcerated for intentional injury were statistically significantly lower than those of both amateur combat athletes and control group participants (p < 0.001). Additionally, a significant reduction in overall aggression scores was observed among prisoners as the number of days in custody increased (p = 0.045). No significant differences were found among amateur combat athletes concerning the discipline variable, and no meaningful relationship was identified between years of active sports participation and aggression scores. Conclusion The findings indicate that educational, social, and sports activities organized in correctional facilities can be effective in reducing aggression levels among inmates. Systematic planning, professional implementation, and continuous evaluation of such programs can make significant contributions to the rehabilitation of prisoners and their successful reintegration into society.